Development of Dila Bisa Media Based on Lectora Inspire in Arabic Language Learning - Majda Qudsiyatul Malikh; Ahmad Mubaligh; Alvira Nirma Wijayanti (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2024)
This research aimed to develop and measure the effectiveness of the "Dila Bisa" learning media and education method based on Lectura Inspire. Researchers used a development model research methodology, ADDIE. The research sample consisted of 47 students and two experts as subjects. Data was collected through observation, interviews, questionnaires, and tests and then analyzed using the Miles and Huberman method for qualitative data and the T-test for quantitative data. The research results showed: 1) that it consisted of five development stages, namely: Analysis, Design, Development, Implementation, and Evaluation. 2) It was found that the educational media "Dila Bisa" had met validity standards and had achieved subject expert test results reaching 86% and educational method expert test results reaching 90%. Additionally, from the field test, the T-test results were obtained at 0.021 < 0.05. Based on the test results, it was concluded that this media was effectively used in learning Arabic.